An introduction to error analysis : the study of uncertainties in physical measurements - Taylor, John R. (John Robert), 1939- (University Science Books, 1997)
The need for error analysis is captured in the book's arresting cover shot - of the 1895 Paris train disaster (also available as a wall poster). The early chapters teach elementary techniques of error propagation and statistical analysis to enable students to produce successful lab reports. Later chapters treat a number of more advanced mathematical topics, with many examples from mechanics and optics. End-of-chapter problems include many that call for use of calculators or computers, and numerous figures help readers visualize uncertainties using error bars. "Score a hit! ...the book reveals ... The need for error analysis is captured in the book's arresting cover shot - of the 1895 Paris train disaster (also available as a wall poster). The early chapters teach elementary techniques of error propagation and statistical analysis to enable students to produce successful lab reports. Later chapters treat a number of more advanced mathematical topics, with many examples from mechanics and optics. End-of-chapter problems include many that call for use of calculators or computers, and numerous figures help readers visualize uncertainties using error bars. "Score a hit! ...the book reveals the exceptional skill of the author as lecturer and teacher...a valuable reference work for any student (or instructor) in the sciences and engineering." The Physics Teacher "This is a well written book with good illustrations, index and general bibliography...The book is well suited for engineering and science courses at universities and as a basic reference text for those engineers and scientists in practice."